Penguatan Karakter Kepemimpinan Kader Aisyiyah dalam Bingkai Pelatihan dan Pengabdian Dosen Interdisipliner - Dendy Eta Mirlana; Sunarso Sunarso; Riza Dessy Nila Ayutika; Ria Fajar Nurhastuti; Amrih Yuwono; Tri Rahayu Ningsih; Dyah Erlina Sulistyaningrum (BADAN PENERBIT STIEPARI PRESS, 2025)
The issue of women’s leadership, particularly in religious organizations such as Aisyiyah, faces ongoing challenges in the optimal development of leadership character. Strengthening leadership character is essential to ensure that female cadres possess resilience, integrity, and managerial competence to take on strategic roles in society. This program was carried out as a community service initiative with the aim of enhancing the leadership capacity of Aisyiyah cadres through an integrated training program facilitated by an interdisciplinary team of lecturers. The methods applied included interactive training, focused group discussions (FGDs), case simulations, and personal reflection exercises, all designed to develop leadership grounded in progressive Islamic values that emphasize justice, equality, and responsibility. The results revealed that the cadres showed increased understanding of leadership principles, greater confidence in assuming organizational responsibilities, and improved ability in planning and making strategic decisions. Furthermore, the interdisciplinary approach encouraged collaboration and broadened perspectives in addressing challenges within the organization. This initiative confirms that community-based leadership training rooted in both values and practical application can effectively build leadership character among women in faith-based organizations. In addition, the program contributes to strengthening Aisyiyah’s institutional capacity while empowering female cadres to play transformative roles in advancing society.